Second booster dose improves antibody neutralization against BA.1, BA.5 and BQ.1.1 in individuals previously immunized with CoronaVac plus BNT162B2 booster protocol - Campos, Guilherme R. F.; Almeida, Nathalie Bonatti Franco; Filgueiras, Priscilla Soares; Corsini, Camila Amormino; Gomes, Sarah Vieira Contin; de Miranda, Daniel Alvim Pena; de Assis, Jéssica Vieira; Silva, Thaís Bárbara de Souza; Alves, Pedro Augusto; Fernandes, Gabriel da Rocha; de Oliveira, Jaquelline Germano; Rahal, Paula; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction SARS-CoV-2 vaccines production and distribution enabled the return to normalcy worldwide, but it was not fast enough to avoid the emergence of variants capable of evading immune response induced by prior infections and vaccination. This study evaluated, against Omicron sublineages BA.1, BA.5 and BQ.1.1, the antibody response of a cohort vaccinated with a two doses CoronaVac protocol and followed by two heterologous booster doses. Methods To assess vaccination effectiveness, serum samples were collected from 160 individuals, in 3 different time points (9, 12 and 18 months after CoronaVac protocol). For each time point, individuals were divided into 3 subgroups, based on the number of additional doses received (No booster, 1 booster and 2 boosters), and a viral microneutralization assay was performed to evaluate neutralization titers and seroconvertion rate. Results The findings presented here show that, despite the first booster, at 9m time point, improved neutralization level against omicron ancestor BA.1 (133.1 to 663.3), this trend was significantly lower for BQ.1.1 and BA.5 (132.4 to 199.1, 63.2 to 100.2, respectively). However, at 18m time point, the administration of a second booster dose considerably improved the antibody neutralization, and this was observed not only against BA.1 (2361.5), but also against subvariants BQ.1.1 (726.1) and BA.5 (659.1). Additionally, our data showed that, after first booster, seroconvertion rate for BA.5 decayed over time (93.3% at 12m to 68.4% at 18m), but after the second booster, seroconvertion was completely recovered (95% at 18m). Discussion Our study reinforces the concerns about immunity evasion of the SARS-CoV-2 omicron subvariants, where BA.5 and BQ.1.1 were less neutralized by vaccine induced antibodies than BA.1. On the other hand, the administration of a second booster significantly enhanced antibody neutralization capacity against these subvariants. It is likely that, as new SARS-CoV-2 subvariants continue to emerge, additional immunizations will be needed over time.